Reactive-cysteine profiling for drug discovery - Maurais, Aaron J. (Curr Opin Chem Biol, 2019)
The recognition that only a small percentage of known human gene products are druggable using traditional modes of non-covalent ligand design, has led to a resurgence in targeted covalent inhibitors. Covalent inhibitors offer advantages over non-covalent inhibitors in engaging otherwise challenging targets. Reactive cysteine residues on proteins are a common target for covalent inhibitors, whereby the high nucleophilicity of the cysteine thiol under physiological conditions provides an ideal anchoring site for electrophilic small molecules. A chemical-proteomic platform, termed isoTOP-ABPP, allows for profiling cysteine reactivity in complex proteomes and is one of many techniques that can aid in two aspects of the covalent-inhibitor development process: (1) to identify novel functional cysteines that lead to modulation of protein function through covalent modification; and, (2) to determine cellular targets and evaluate promiscuity of electrophilic fragments, small molecules, and natural products. Herein, we discuss recent advances in isoTOPABPP and potential applications of this technology in the drug-discovery pipeline.